Penerapan Metode Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) Sebagai Pendukung Keputusan Pemilihan Penerima Program Mahasiswa Wirausaha (Studi Kasus : Universitas Sriwijaya) - Rahmat Dwian; Anita Desiani; Sugandi Yahdin (Jurnal Teknologi, 2021)
Program Mahasiswa Wirausaha (PMW) of Sriwijaya University is one of the facilities for Sriwijaya University students who have an interest in entrepreneurship. There are 5 criteria in selecting PMW proposals based on Sriwijaya University, namely product innovation and originality, market potential/market opportunities, production processes, organization, and investment plans. In PMW 2019, there were 304 proposals submitted and 146 proposals were approved for funding. The proposal selection process by Sriwijaya University only accumulates the judges' scores for each criterion manually. In this study, the MOORA method was applied as decision support which proposals were eligible to fund. Starting from weighting the criteria, calculating the normalized matrix, multiplying each criterion weight by the normalized matrix, and sorting the product from highest to lowest. In the calculation results, there is a data similarity of 92.97% in the results of the MOORA method with the results from Sriwijaya University. This shows that the MOORA method can be used as a consideration in selecting PMW proposals for the following year.